The Gambia : Fourth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Request for a Waiver of Nonobservance of Performance Criterion, Augmentation of Access, and Modification of Performance Criteria; Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for The Gambia. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This paper presents key findings of the Fourth Review for the Gambia under the three-year arrangement under the Poverty Reduction and Growth Facility (PRGF). The Gambia remains at high risk of debt distress. Overall performance under the PRGF-supported program has been satisfactory, but downside risks to achieving program objectives have increased. IMF staff supports the authorities' requests for a waiver for nonobservance of the fiscal basic balance performance criterion, augmentation of access, and modification of quantitative performance criteria for end-March 2009.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet